Translation and cultural adaptation of Brazilian Detailed Assessment of Speed of Handwriting: conceptual and semantic equivalence - Cardoso, Monique Herrera; Henderson, Sheila; Capellini, Simone Aparecida [UNESP] (Academia Brasileira de Audiologia, 2014)
PurposeTo perform the translation and cultural adaptation of the Detailed Assessment of Speed of Handwriting (DASH) for the Brazilian population.Method(1) Evaluation of conceptual and items equivalence, and (2) Semantic equivalence, including the steps of (2a) Translation, (2b) retranslation, (2c) Review by the committee of judges and (2d) Pre-test. The second step was carried out by two professionals and 2b by two other professionals, 2c was formed by speech therapists, occupational therapists and educators and the 2d was carried out with 32 students, four from each age group (9-16 years old).Result(1) It was found that the concepts and items are equivalent in both cultures (British and Brazilian). In the second stage it was found that two tasks in the original procedure, pangrama classified as a phrase in the English language is used. Therefore, when performing unification of translations, an adjustment was made for the phrase pangrama in Portuguese. In 2b showed that the translation was valid and 2c was consolidated all versions produced in a single version in Portuguese, which was applied in school. In 2d there was acceptance and understanding of the students in the proposed tasks and internal consistency value of 0.701, others words, satisfactory variability. ConclusionThis procedure can be applied in the Brazilian population, however new studies are being developed with the objective of providing greater reliability and validity of the instrument.

Objetivo Realizar a tradução e a adaptação cultural do Detailed Assessment of Speed of Handwriting (DASH) para a população brasileira. Métodos (1) Avaliação de equivalências conceitual e de itens e (2) Avaliação da equivalência semântica, que envolveu as etapas de (2a) Tradução, (2b) Retradução, (2c) Revisão pelo comitê de juízes e (2d) Pré-teste. A etapa 2a foi realizada por dois profissionais e a 2b por outros dois profissionais; na etapa 2c foi composto por um comitê de juízes fonoaudiólogas, pedagogas e terapeutas ocupacionais e a 2d foi realizada com 32 escolares, sendo quatro de cada faixa etária (de 9 a 16 anos). Resultados(1) Verificou-se que os conceitos e os itens são equivalentes nas duas culturas (britânica e brasileira). Na etapa 2a, observou-se que, em duas tarefas do procedimento original, foi utilizada uma frase classificada como pangrama na língua inglesa. Diante disso, ao se realizar a unificação das traduções, foi feita uma adaptação da frase para um pangrama na língua portuguesa. Na etapa 2b, verificou-se que a tradução foi válida e na 2c, todas as versões produzidas foram consolidadas em uma única versão, em português, que foi aplicada aos escolares. Na etapa 2d, constatou-se aceitabilidade e compreensão dos escolares nas tarefas propostas e valor de consistência interna de 0,701, ou seja, variabilidade satisfatória. Conclusão O DASH pode ser aplicado na população brasileira. Entretanto, novos estudos estão sendo desenvolvidos, com o objetivo de propiciar maior confiabilidade e validade ao instrumento.
Tradução e adaptação cultural brasileira do Detailed Assessment of Speed of Handwriting: equivalência conceitual e semântica
Keywords: Escrita manual; Avaliação; Comparação transcultural; Tradução; Fonoaudiologia; Handwriting; Assessment; Cross-cultural comparison; Translating; Speech; language and hearing sciences